Polymer adsorption isotherms with NaCl and CaCl2 on kaolinite substrates - Jaime José Martínez Vertel (Dyna, 2019)
During polymer – flooding, polymer’s molecules are attached to the surface of the rock as a result of many interactions between both components, leading to a decrease on the injected slug’s concentration. This phenomenon, known as adsorption, depends on rock type, degree of hydrolysis and polymer concentration, reservoir’s temperature, water salinity, among others, and might be predicted by analytical models. This work shows the results of a series of static tests in which water’s salinity (NaCl and CaCl2) and polymer’s concentration were varied, to determine which of the analytical models can predict in a better way the experimental data when kaolinite substrates are used. It is discussed the abnormal trend of the adsorption, where higher NaCl concentrations resulted in lower adsorption results, basically because of a flocculation.